Engagement, Disengagement, or Exit: A Theory of Equilibrium Associations. Issue 2 (23rd July 2015) - Penn, Elizabeth Maggie
Abstract : This article considers the possibility of mutually beneficial communication among groups when any group may choose to unilaterally join or exit an alliance. My main concern is the trade‐off groups face between the informational benefits of associating with others in a large society versus the costs imposed by power sharing and preference diversity. When these costs are sufficiently high, groups may prefer exit to association. The results of this article characterize the associations of groups that can be sustained in equilibrium, and within those associations, the types of groups that choose to meaningfully communicate with others. The results demonstrate that there can be benefits or costs associated with the inclusion of preference extremists in a diverse society, whether or not those extremists choose to actively communicate with outgroups. The results also speak to institutional mechanisms for fostering communication across diverse groups.